FACTORS AFFECTING ACCEPTANCE OF AUDITOR'S DYSFUNCTIONAL BEHAVIOR AND CONSEQUENCES ON THE QUALITY OF AUDIT RESULTS AT PUBLIC ACCOUNTING OFFICES IN BALI - Dewi, I Gusti Ayu Ratih Permata; Dewi, Cok Istri Ratna Sari (International Journal of Social Science, 2022)
This study aims to analyze work stress, time budget pressure, locus of control and auditor personality type on auditor dysfunctional behavior and its consequences on the quality of audit results. The theories used in this research are Theory of Attitudinal Change. The independent variables of this research are work stress, time budget pressure, locus of control and personality type. The dependent variable is the quality of the audit results. Also, the mediating variable is auditor dysfunctional behavior. This research was conducted at a registered public accounting firm in Bali using a questionnaire distributed to auditors who at least become team leaders in audit assignments. The data analysis technique used is the Partial Least Square (PLS) approach. The results showed that audit time budget pressure and locus of control had a positive effect on work stress. Furthermore, work stress, audit time budget pressure and locus of control have a positive effect on audit quality reduction behavior. The results also show that work stress, time budget pressure, external locus of control and personality type have a positive effect on auditor dysfunctional behavior. Furthermore, the dysfunctional behavior of auditors has a negative effect on the quality of audit results.